An Analysis of Students' Essay Thematic Structure in English Academic Writing Course - Mukhamirudin, Afrianto Akhmad (Allure Journal, 2025)
Academic writing has always been a fundamental skill for higher education students, yet it is still perceived to be a difficult skill to acquire. Accordingly, educators are encouraged to find ways to solve this issue. A concept taken from the Systemic Functional Linguistics (SFL) theory, namely thematic structure, can be a solution that provides a detailed description of how cohesion and coherence can be structured in a text. Therefore, this descriptive qualitative research is trying to provide a clear description of students’ thematic structure in English academic writing courses. The primary methodology framework to analyze and interpret the collected data adopted the SFL thematic structures model from Halliday and Matthiessen (2014), named textual metafunction, which identified themes into topical, textual, and interpersonal themes. The findings showed that students tended to employ topical themes, specifically unmarked topical themes, to realize the ideas in their clauses. Conjunctive adjuncts as the textual theme were frequently used by the students to build connections between clauses in the text, while conjunction was barely employed. The interpersonal theme was the least common type of theme employed by the students. However, this situation is quite common in academic writing as personal judgment is avoided to create a more objective text. Thus, future research is encouraged to analyze thematic structure in various texts and contexts